Investigation of the effect of FDM process parameters on mechanical properties of 3D printed PA12 samples using Taguchi method. (January 2023) - Kam, Menderes; İpekçi, Ahmet and Şengül, Ömer
This study investigated the effects of FDM (Fused Deposition Modeling) process parameters on mechanical properties (tensile strength, elongation, and impact strength) of 3D (three-dimensional) printed PA12 (Polyamide12) samples using Taguchi method. In the experimental design (L8 ), four different layer thickness (0.1, 0.15, 0.2, 0.25 mm), extruder temperature (250 and 260°C), filling structure (Rectilinear and Full Honeycomb), and occupancy rate (25 and 50%) were determined. The tensile and impact strength test samples were printed with the FDM method. Tensile and impact strength of the test samples were carried out according to ISO 527 and ISO 180 test standards. The findings obtained from tests were analyzed and compared. As a result, the layer thickness is most effective factor for enhance the mechanical properties instead extruder temperature, occupancy rate, and filling structure. The optimum tensile strength of determined for process parameters (layer thickness, occupancy rates, filling structures and extruder temperature) were 0.25 mm, 50%, Rectilinear, and 250°C, respectively. The optimum impact strength of determined for process parameters (layer thickness, occupancy rates, extruder temperature, and filling structures) were 0.25 mm, 50%, 250°C, and Rectilinear, respectively. PA12 filament material can be used to printing for sleeve bearing due to their mechanical properties. It can be used in the production of many machine parts and components due to its tensile strength, impact strength resistance and damping properties.